Political power and economic policy : theory, analysis, and empirical applications - Rausser, Gordon C.; Swinnen, Johan F. M., 1962-; Zussman, Pinchas (Cambridge, U. K. : Cambridge University Press, 2011)
'This book analyzes the links between political economics, governance structures and the distribution of political power in economic policy making. The book theoretically explains and empirically quantifies these interactions. The analysis includes both public good policies and redistributive policies. Part I of the book presents the conceptual foundations of political-economic bargaining and interest group analysis. After presenting the underlying theory, Part II of the book examines ideology, prescription and political power coefficients; Part III analyzes a number of specific structures; and Part IV presents a framework for political econometrics with a number of empirical applications and testable hypotheses. In all four parts of the book, four analytical dimensions of public policy are distinguished: governance structures, political economy, mechanism design and incidence'--Provided by publisher.
Includes bibliographical references (p. 489-514) and index.
Keywords: Power (Social sciences); Economic policy